1990
DOI: 10.1063/1.458943
|View full text |Cite
|
Sign up to set email alerts
|

Wave functions of helium clusters

Abstract: The ground and several l=0 breathing mode vibrational excited state wave functions of HeN clusters are determined for N=3–5, 20, 70, and 240, using the variational Monte Carlo method. These wave functions incorporate one-, two-, and three-particle correlation effects and give binding energies, density profiles, and vibrational excitation energies accurately. The larger clusters have liquid-like structure, characterized by a pair distribution function showing approximately two coordination shells. The smallest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 34 publications
3
39
1
Order By: Relevance
“…For the case of the helium trimer this is different. In 4 He 3 there is apart from the ground state only one other predicted 18 Barletta and Kievsky 19 Gonzalez-Lezana et al 22 Paola et al 33 Blume et al 34 Figure 1 | Internuclear two-body distances. (a) Experimental distribution of the 4 He- 4 He distance of 4 He 3 and the 4 He- 3 He distances of 3 4 He- 4 He comparison with theoretical predictions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of the helium trimer this is different. In 4 He 3 there is apart from the ground state only one other predicted 18 Barletta and Kievsky 19 Gonzalez-Lezana et al 22 Paola et al 33 Blume et al 34 Figure 1 | Internuclear two-body distances. (a) Experimental distribution of the 4 He- 4 He distance of 4 He 3 and the 4 He- 3 He distances of 3 4 He- 4 He comparison with theoretical predictions.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is theoretical consensus concerning the floppy nature of both the 4 He 3 and 3 He 4 He 2 molecules, the geometrical shape is a matter of extensive current debates. In the particular case of the 4 He 3 trimer some calculations suggest an equilateral triangular structure [18][19][20] , while others indicate a significant contribution of linear configurations 21,22 . It has also been recently suggested that this controversy is often mislead by drawing false conclusions from correctly calculated distributions 3 .…”
mentioning
confidence: 99%
“…(5) and (6) does not give a good variational energy and we additionally include a variational Fermi function which depends on the distance R j of the jth atom to the center of mass of the cluster [38],…”
Section: B Numerical Treatment Of N -Body Clustersmentioning
confidence: 99%
“…The experimental research has faced the difficulties of size detecting the clusters. Recently, molecular beam diffraction from a transmission gratting [5] has proven to be successful to detect even the 4 He dimer [6], giving further impetus to the study of helium clusters.As the atom-atom interaction is well-known and relatively simple, the solution of the Schrödinger equation has been obtained using several microscopic methods, mainly based on Monte Carlo techniques [7,8,9,10,11]. Variational Monte Carlo (VMC) calculations, using a Jastrow-like ansatz for the many-body wave function, are currently used for systems dominated by strong shortrange interactions.…”
mentioning
confidence: 99%
“…As the atom-atom interaction is well-known and relatively simple, the solution of the Schrödinger equation has been obtained using several microscopic methods, mainly based on Monte Carlo techniques [7,8,9,10,11]. Variational Monte Carlo (VMC) calculations, using a Jastrow-like ansatz for the many-body wave function, are currently used for systems dominated by strong shortrange interactions.…”
mentioning
confidence: 99%